乳幼児家族へのハイブリッド看護に関する認識とヘルスリテラシーとの関連 - 岩﨑 順子 (日本母性看護学会誌, 2025)
We conducted a survey questionnaire targeting families of infants and nurses to clarify how the awareness of hybrid nursing care and health literacy are related and compared the results between families and nurses. Responses were obtained from 345 families and 56 nurses (response rate/valid response rate: 7.67%/97.73% for families, 37.66%/96.55% for nurses). Of the 16 nursing items for families of infants, face-to-face methods were most frequently selected by both families and nurses (11 items) including health checkups for mothers and infants, while multiple nursing methods were selected for items related to information provision. The number of methods selected for nursing care was significantly higher for nurses than for families, thereby suggesting the possibility of hybrid nursing care in which nursing care is provided to families using various methods. In addition, health literacy was significantly higher among families and nurses who chose educational material provision, thus indicating that health literacy was related to the choice of nursing method. 本研究では、乳幼児家族へのハイブリッド看護の認識とヘルスリテラシーとの関連について、乳幼児家族及び看護職者との比較を通して明らかにすることを目的とした。乳幼児家族・看護職者を対象にアンケート調査を実施した結果、家族345名、看護職者56名より回答が得られた（回収／有効回答率：家族7.67／97.73％、看護職者37.66／96.55％）。乳幼児家族への16の看護について家族・看護職者共に母児の健康診査を含む11の項目で対面による方法での選択が最も多い一方、情報提供に関する項目では教材を含む複数の看護方法の選択がみられた。看護方法に関する選択数は家族と比較して看護職者で有意に多く、様々な方法で家族へ看護を実践していくハイブリッドによる看護の可能性が示唆された。また、教材での方法を選択した家族・看護職者でヘルスリテラシーは有意に高い結果であり、ヘルスリテラシーが看護方法の選択に関連していた。